EFEKTIVITAS PEMBERIAN PSIKOEDUKASI MENGENAI SELF-AWARENESS PADA SISWA DI SMA KARTIKA XX-I MAKASSAR - Jaya Lestari; Husnul Indira Rahman; Dwi Nurhasanah K; Andi Nurul Izzah Ilham; Ahmad Ridfah (Jurnal Kebajikan: Pengabdian Kepada Masyarakat, 2023)
High school students need to understand themselves to achieve an optimal self-development, in order to determine life goals and prepare themselves to face bigger life challenges in the future. Self-awareness is one of the skills that students needs to improve to be able to grow and develop themselves. This research was presented in the form of psychoeducation in the form of providing material about self-awareness and was given using the lecture method which is accompanied by giving a pre-test before the material is given, a post-test after the material is given, and reflections about their strengths and weaknesses. This study aims to determine the effectiveness of providing psychoeducation regarding self-awareness to students at SMA Kartika XX-I Makassar. The effectiveness of providing psychoeducation can be seen from the increase in the number of participants who answered correctly on the given pretest and posttest questions. Psychoeducation was carried out offline in several classrooms at SMA Kartika XX-I Makassar and was attended by 50 students. The material provided includes the definition of self-awareness, aspects of self-awareness to efforts to increase self-awareness. Based on the results of the analysis of psychoeducation, it can be concluded that the provision of psychoeducation to students at SMA Kartika XX-I Makassar is effective with an increase in participants' understanding of self-awareness after giving the material. This is evidenced from the results of the pre-test and posttest that shows the students' sunderstanding of self-awareness had increased.